Rancang Bangun Sistem Informasi Pengolahan Data Karyawan Absensi Berbasis Web Pada CV. Cahaya Prima Printing - Fachruddin, Ilham; Laksono., M.KOM., DR. Sularso Budi (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
A web-based employee management information system is an important requirement for companies to improve efficiency and reduce employee management weaknesses. CV. Cahaya Prima Printing as a printing company requires a web-based employee management information system to help manage the home manage employee data, attendance and work schedules. This study aims to design and implement a web-based employee management information system at CV. Prime Light Printing. The research methodology used is a systems approach, with stages of user needs analysis, business process analysis, database design, interface design, system implementation, system testing and evaluation. The results of the study show that a web-based employee management information system can help CV. Cahaya Prima Printing in managing employee data effectively and efficiently. This system has features that can help employee management, such as attendance management, work schedule management, employee permissions and menu management. System testing shows that this system runs well and is reliable. Suggestions for the development of this system are to improve system security so that employee data is properly maintained.